2018
DOI: 10.3390/economies7010001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Spillover Effects between Foreign Exchange Rate Volatility and Commodity Price Volatility in Uganda

Abstract: This study investigates the impact of commodity price volatility spillovers on financial sector stability. Specifically, the study investigates the spillover effects between oil and food price volatility and the volatility of a key macroeconomic indicator of importance to financial stability: the nominal Uganda shilling per United States dollar (UGX/USD) exchange rate. Volatility spillover is examined using the Generalized Vector Autoregressive (GVAR) approach and Multivariate Generalized Autoregressive Condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
2
11
0
3
Order By: Relevance
“…Similarly, this study shows that real exchange rate volatility has a deleterious effect on the impact of financial development on economic growth in the West African region. This is consistent with the theoretical literature which contended that high and volatile real exchange rate has the potential to diminish international trade, weaken macroeconomic stability, distort price transparency and inhibit international financial integration (see Bleaney and Greenaway 2001;Katusiime 2019;Razmi et al 2012). Thus, real shocks and financial shocks are related, since the latter are significantly amplified in countries with high exchange rate fluctuations.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, this study shows that real exchange rate volatility has a deleterious effect on the impact of financial development on economic growth in the West African region. This is consistent with the theoretical literature which contended that high and volatile real exchange rate has the potential to diminish international trade, weaken macroeconomic stability, distort price transparency and inhibit international financial integration (see Bleaney and Greenaway 2001;Katusiime 2019;Razmi et al 2012). Thus, real shocks and financial shocks are related, since the latter are significantly amplified in countries with high exchange rate fluctuations.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
“…Besides its direct effect on economic growth, studies have shown that real exchange rate and financial development could have a dynamic relationship. Lin and Ye (2011) posited that financial development has a significant effect on the choice of exchange rate regime, whereas Katusiime (2018) reported that exchange rate has a significant effect on the growth of private sector credit. Thus, countries with less developed financial markets are more likely to adopt a fixed exchange rate, while countries with higher levels of financial development are more likely to adopt a flexible system, which in turn determines the exchange rate.…”
Section: Introductionmentioning
confidence: 99%
“…Oil is a large commodity and, as such, it determines significant volatilities and fluctuations in price to a greater extent than other more stable investments (Chang, McAleer, & Wang, 2018). According to this theory, there are many spillover effects of oil prices; for example, oil prices are affected by a variety of factors and spillovers, as they are particularly responsive to decisions about outputs developed by oil authorities (Katusiime, 2019). Similar to any other product or good, laws and supply and demand also have a VS effect on the prices of oil, and bank prices and production costs have a spillover effect on oil prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical findings denoted that the effect of commodity demand shocks on commodity prices was much greater than that in commodity supply shocks. Katusiime (2019) applied GARCH and Generalized Vector Autoregressive (GVAR) models to investigate the relationship between Uganda's commodity price fluctuations and financial sector stability, and found that the link between the two is close except the financial crisis. Moreover, oil and agricultural product price fluctuation is one of the main drivers of commodity price fluctuation.…”
Section: Literature Reviewmentioning
confidence: 99%